2021
DOI: 10.2991/assehr.k.210715.101
|View full text |Cite
|
Sign up to set email alerts
|

Should I Quit? Understanding Job Stress and Coping Strategies Among Hospitality Students During on the Job Training Program

Abstract: One of the important components of vocational education curriculum is the "on the job training program" which provides both opportunities and challenges for students in a workplace-based setting. Through this program, hospitality students experience and become part of hotel's daily operations which thus expectedly improves their attitude, skills, and knowledge. At the same time, students encounter challenging situations that may trigger job stress. This study aimed at understanding the types of job-related str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The findings also revealed that there is a positive impact of avoidance coping strategies on occupational stress. This finding is in line with the findings of prior studies (e.g., Duscheket al, 2020;Elziny & Kamel, 2020;Trianasari & Rahmawati, 2020;Chua et al, 2022). Employees adopting an avoidance strategy choose to focus more on pleasant than unpleasant situations and try to divert their attention from a problem by occupying themselves with other activities to reach temporary comfort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings also revealed that there is a positive impact of avoidance coping strategies on occupational stress. This finding is in line with the findings of prior studies (e.g., Duscheket al, 2020;Elziny & Kamel, 2020;Trianasari & Rahmawati, 2020;Chua et al, 2022). Employees adopting an avoidance strategy choose to focus more on pleasant than unpleasant situations and try to divert their attention from a problem by occupying themselves with other activities to reach temporary comfort.…”
Section: Discussionsupporting
confidence: 90%
“…The ability to deal with stressful situations depends on an individual's thinking style or personality features (Kahar & Wee, 2020). People will choose one coping method over another based on how well they feel they can manage their stressors and how much access they have to coping resources (Trianasari & Rahmawati, 2020). Resources that a person might use to deal with emotional stress are referred to as "coping resources".…”
Section: Coping Strategies and Occupational Stressmentioning
confidence: 99%
“…This study intersects with the bodies of research on students' learning processes, students' experiences, as well as industries' and universities' evaluative frameworks. It extends the concept of students' (in)authentic experiences that have already been explored in extant research (e.g., Ducan et al, 2011;Grant-Smith et al, 2017;Hughes, 1998;Pulakos et al, 2015;Trianasari & Rahmawati, 2021;Wood, 2004) by arguing that these experiences are constituted by students' personalities and aspirations to find values that are true to themselves. It does so by raising students' voices in framing evaluative models that, to date, have only included employers' and institutions' perspectives.…”
Section: Introductionmentioning
confidence: 62%
“…Self-esteem is often defined as students' belief and confidence in their own abilities and values (e.g., Grant-Smith, 2017;Jackson, 2014;Trianasari & Rahmawati, 2021;Wilt et al, 2019). Jackson (2014) analyzed survey data from 131 undergraduates studying diverse disciplines at an Australian higher education institution to explore the impacts of OJT design and content on student employability skills.…”
Section: Self-esteemmentioning
confidence: 99%
See 1 more Smart Citation